2019
DOI: 10.1002/ijc.32209
|View full text |Cite
|
Sign up to set email alerts
|

Androgen receptor expression in circulating tumor cells of patients with metastatic breast cancer

Abstract: The androgen receptor (AR) has potential clinical relevance in metastatic breast cancer (mBC) since it might be a treatment target and has been associated with endocrine resistance. A minimal‐invasive way to determine AR expression on metastatic tumor cells is by characterization of circulating tumor cells (CTCs). Here, we assessed AR mRNA expression in CTCs (CTC‐AR) and in matched primary tumor samples from mBC patients representing different breast cancer subtypes. In addition, we explored CTC‐AR‐status in r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 34 publications
0
20
1
Order By: Relevance
“…Up to now, only very few groups have addressed the expression of prostate cancer related genes on CTCs in BC (29)(30)(31)(32)(33)46). Most of these studies analyzed CTCs of metastatic HR+/HER2-BC patients for the expression of AR with a detection rate ranging from 20 to 43%, respectively (29,(31)(32)(33). Krujiff et al, further compared AR expression in primary tumor tissues and matched CTCs and observed switches from AR+ to AR-negative and vice versa with an overall disconcordance of 58% (32).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Up to now, only very few groups have addressed the expression of prostate cancer related genes on CTCs in BC (29)(30)(31)(32)(33)46). Most of these studies analyzed CTCs of metastatic HR+/HER2-BC patients for the expression of AR with a detection rate ranging from 20 to 43%, respectively (29,(31)(32)(33). Krujiff et al, further compared AR expression in primary tumor tissues and matched CTCs and observed switches from AR+ to AR-negative and vice versa with an overall disconcordance of 58% (32).…”
Section: Discussionmentioning
confidence: 99%
“…Most of these studies analyzed CTCs of metastatic HR+/HER2-BC patients for the expression of AR with a detection rate ranging from 20 to 43%, respectively (29,(31)(32)(33). Krujiff et al, further compared AR expression in primary tumor tissues and matched CTCs and observed switches from AR+ to AR-negative and vice versa with an overall disconcordance of 58% (32). In abiraterone/prednisone-treated postmenopausal ER+ advanced BC patients neither the analysis of biomarkers in serum, CTCs nor tumor tissue identified a subgroup a patients with significantly improved PFS, although dual expression of AR and ER in baseline CTCs were supposed to have an association with improved PFS (47).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The application of single cell analysis technologies to PDX models has shown that CTCs are continuously released by the primary tumour, however only a proportion of clones have the capacity to seed a metastatic deposit, and as such the utility of CTCs in predicting the characteristics of subsequent metastases may be limited [111]. Nevertheless, analysis of CTCs can capture phenotypic heterogeneity of the tumour of origin, for example in the expression of ER, HER2 and androgen receptors [112][113][114], and also of biological processes driving metastasis such as dynamic changes in epithelial and mesenchymal composition [115,116]. Clusters of CTCs, which may show intermediate epithelial/mesenchymal properties [115,117], demonstrate higher metastatic capacity than single cells [118][119][120][121].…”
Section: Capturing Intra-tumour Heterogeneity In Tissue or Liquid Biopsymentioning
confidence: 99%